{Cd3}-MOF hybrid material containing multiple trinuclear clusters, preparation method thereof and application of {Cd3}-MOF hybrid material in preparation of adjustable white light HLED
By preparing {Cd3}-MOF hybrid materials containing a variety of tri-core clusters, the problems of inorganic phosphor recycling and rare earth resources are solved, efficient preparation of rare earth-free raw materials and the application of adjustable white light HLEDs, and new fluorescent materials are provided Application prospects.
Patent Information
- Application Number
- CN202410801277.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-06-20
- Publication Date
- 2024-12-13
- Estimated Expiration
- 2044-06-20
AI Technical Summary
The existing inorganic phosphors are difficult to recycle, and the rare earth-based phosphor resources are not renewable, making it difficult to predict the structure and structure-effect relationship of metal-organic hybrid materials, which limits its application in the LED field.
The {Cd3}-MOF hybrid material containing a variety of trinuclear clusters was prepared by solvothermal synthesis method. The chemical formula is {[Cd12(npd)12(tpt)4(H2O)2](H2O)10}n , with a three-dimensional metal-organic frame structure and high porosity, used to prepare adjustable white light HLEDs.
It realizes high-efficiency preparation without rare earth materials, with good thermal stability and high yield. The manufactured HLED can emit white light in visible light area of 400-760nm, and can adjust the spectrum according to the current intensity, providing the application of new fluorescent materials. prospect.
Smart Images

Figure CN119119493A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the field of advanced fluorescent materials, and specifically relates to {Cd 3}-MOF hybrid materials, their preparation methods and their applications in the preparation of tunable white light HLEDs. Background Art
[0002] Traditional light-emitting diodes (LEDs) are energy-saving, long-life, and small in size. They are widely used in indication, display, and lighting, and are the most important lighting revolution in the 20th century. Since the 1960s, red and orange LEDs have been invented using semiconductor luminescent materials containing gallium (Ga), arsenic (As), phosphorus (P), and nitrogen (N). After the advent of blue diodes in the late 1980s, chip coating with inorganic phosphors became the mainstream technology for manufacturing LEDs, and the resulting LEDs are also called "electro-optical" LEDs. Since both the chip luminescent body and phosphor are inorganic and do not contain carbon and hydrogen elements, they are also called inorganic light-emitting diodes in the industry. The inorganic phosphors used are mainly mixtures or composites containing multiple metal oxides, with a total metal element content of more than 60%, a high density, and are difficult to recycle.
[0003] In the chemical industry, inorganic-organic hybrid materials (Hybrid Material) refer to solid functional materials composed of inorganic and organic substances, which can be simply divided into disordered hybrid materials (mixtures) and ordered hybrid materials (pure substances); ordered hybrid materials are pure substances obtained by chemical reactions between inorganic and organic raw materials. They have clear structures, low densities, diverse properties, and wide applications. They contain few types of metal elements and are conducive to degradation and recycling. They are the key research objects in the field of new materials. Since 1987, the ordered hybrid material 8-hydroxyquinoline aluminum (abbreviated as AlQ 3 ) have been used to manufacture light-emitting devices, fluorescent metal-organic hybrid materials, including metal-organic frameworks (MOF), coordination polymers or coordination supramolecular materials, have become important advanced light-emitting materials. The "electro-optical" light-emitting diodes prepared by replacing inorganic phosphors with fluorescent hybrid materials can be called hybrid light-emitting diodes (Hybrid Light-Emitting Diodes), abbreviated as HLED.
[0004] Fluorescent MOF hybrid materials with porous structural characteristics are not only orderly in structure, good in stability, high in light transmittance, and low in density, but also have good luminescence properties. Since rare earths are the "vitamins" of the metallurgical industry and are non-renewable national strategic resources, and ordinary transition metal salts are cheap and readily available, non-rare earth fluorescent MOF hybrid materials have become new materials that have attracted much attention. They may replace or partially replace rare earth-based phosphors to a certain extent. Since the microscopic process of chemical reactions is very complex and there are many influencing factors, it is still difficult to predict the structure and structure-activity relationship of MOF materials, which is a challenging frontier topic. Summary of the invention
[0005] To achieve the above object, the present invention provides the following technical solution: a {Cd 3}-MOF hybrid material, whose general chemical formula is {[Cd 12 (npd) 12 (tpt) 4 (H 2 O) 2 ](H 2 O) 10} n , belongs to the triclinic system, the space group is Pī, the unit cell parameters In the chemical formula, the component npd 2- It is an organic carboxylic acid H 2 npd removes two protons, the H 2 The structure of npd is shown in formula Ⅰ; the structure of component tpt is shown in formula Ⅱ,
[0006]
[0007] Further, in the {Cd 3 The asymmetric unit of the crystal structure of the}-MOF hybrid material contains 12 crystallographically independent Cd 2+ ions, 12 npd 2- , 4 tpt, 2 coordinated water molecules and 10 lattice water molecules; the organic component npd 2- Four coordination modes are adopted to bridge two Cd 2+ ions or 3 Cd 2+ ions or 4 Cd 2+ Ion; Cd 2+ Among the coordination numbers of ions, Cd2, Cd3, Cd5, and Cd11 have a coordination number of 7, and the remaining Cd 2+ The coordination number of the ion is 6; the bond lengths of Cd-O and Cd-N range from Carboxylate, pyridine N and water molecules form four different trinuclear clusters {Cd 3}; organic component npd 2- The coordination modes of tpt and tpt are shown in formulas III to VII, where M represents metal Cd 2+ Ion; Cd 2+ The coordination modes are shown in formulas VIII to XI, and the numbers on the right side of the element symbols represent the atomic numbers in the asymmetric unit.
[0008]
[0009] Further, in the {Cd 3 In the spatial structure of}-MOF hybrid materials, [Cd 3 There is a π…π interaction between the aromatic rings of the (tpt) structural unit, and the interplanar spacing Then form supramolecular chain [Cd 3 (tpt)] n ; The above three-core cluster {Cd 3} can be simplified to 7 connected nodes, organic component npd 2- and tpt components bridge the trinuclear cluster {Cd 3}, forming a composition of [Cd 12 (npd) 12 (tpt) 4 (H 2 O) 2 ] of a three-dimensional metal-organic framework {Cd 3}-MOF, which can be simplified to a 3,7-connected two-node topology network. 3 In}-MOF, there are two different tunnels, A and B, with cross-sectional dimensions of and {Cd 3 The porosity of}-MOF calculated by Platon is 22.6%.
[0010] Further, the {Cd 3}-MOF hybrid materials with H 2 npd, tpt, Cd(NO 3 ) 2 ·4H 2 O and HNO 3 As raw materials, a mixed solution of acetonitrile and water is used as solvent and prepared by solvothermal synthesis method.
[0011] Furthermore, the preparation method specifically comprises the following steps:
[0012] (1) The above raw materials and solvent are mixed to form a reaction system, which is placed in a sealed container; the raw material H 2 npd, tpt, Cd(NO 3 ) 2 ·4H2 O and HNO 3 The molar ratio of the substance is 1:1:2:1.4-7.0; the volume ratio of the solvent acetonitrile and water is 1-9:9-1;
[0013] (2) The reaction system is stirred at room temperature for 10 to 30 minutes, and then the reaction temperature is raised to 100 to 160° C. and reacted for 3 to 5 days, followed by natural cooling, filtration, and drying to obtain block crystals.
[0014] Further, in step (1), H 2 npd, tpt, Cd(NO 3 ) 2 ·4H 2 O and HNO 3 The molar ratio is 1:1:2:3.5.
[0015] Furthermore, H 2 The initial molar concentration of npd was 5 mmol / L.
[0016] Furthermore, the reaction temperature in step (2) is 120° C., and the drying refers to washing the crystals with distilled water and then drying them naturally in air at room temperature.
[0017] The {Cd 3}-MOF hybrid materials are used in the preparation of hybrid light-emitting diodes HLED and composite fluorescent materials. The prepared HLED can emit adjustable white light that changes with the current strength during operation, and the white light wavelength covers the visible light band of 400-760nm.
[0018] Compared with the prior art, the present invention has the following beneficial effects:
[0019] (1) The present invention prepares a plurality of trinuclear clusters {Cd 3}-MOF hybrid material is a crystalline MOF hybrid material synthesized by coordination bond drive. In its crystal structure, the trinuclear cluster {Cd 3} can be simplified to 7 connected nodes, organic component npd 2- and tpt components bridge the trinuclear cluster {Cd 3}, forming a composition of [Cd 12 (npd) 12 (tpt) 4 (H 2 O) 2 ] of a three-dimensional metal-organic framework {Cd 3}-MOF, with a 3,7-connected two-node topology network. {Cd 3 In}-MOF, there are two different tunnels, A and B; {Cd3 The calculated porosity of}-MOF by Platon is 22.6%. These structural features provide a paradigm for the study of new crystalline luminescent materials.
[0020] (2) The present invention prepares {Cd 3}-MOF hybrid materials, organic raw materials and metal salts are easily available, no rare earth raw materials are required, the experimental conditions are mild, the operation is simple, the experimental yield is about 75%, the physical phase purity is high, and it has good thermal stability.
[0021] (3) The present invention provides {Cd 3 The hybrid light-emitting diode HLED is a new type of hybrid light-emitting diode (HLED) that uses a single-component phosphor and is packaged into a 1W purple LED chip through the "electro-optical" technology. When driven with a certain power, it emits adjustable white light with the input current. The wavelength range of the emitted white light is 400-760nm, covering the visible light region. The HLED parameters reveal that the {Cd 3}-MOF hybrid materials are new fluorescent materials with potential application prospects in the LED field. BRIEF DESCRIPTION OF THE DRAWINGS
[0022] Figure 1 For the present invention 3 X-ray powder diffraction pattern of}-MOF hybrid material;
[0023] Figure 2 For the present invention 3 Thermogravimetric curve of}-MOF hybrid material;
[0024] Figure 3 For the present invention 3}-Infrared spectrum of MOF hybrid material;
[0025] Figure 4 For the present invention 3}-MOF hybrid material Cd 2+ Four coordination modes of ions (a) and trinuclear cluster {Cd 3} crystal structure (b);
[0026] Figure 5 For the present invention 3}-MOF hybrid material crystal structure diagram;
[0027] Figure 6 For the present invention 3 Solid-state fluorescence spectrum of}-MOF hybrid material;
[0028] Figure 7 For the present invention 3}-MOF hybrid material encapsulated HLED luminescence spectrum, chromaticity coordinate diagram and photos before and after luminescence;
[0029] Figure 8 For the present invention 3}-MOF hybrid material encapsulated HLED light color parameters as a function of current intensity. DETAILED DESCRIPTION
[0030] The method of the present invention is described in detail below in conjunction with specific embodiments and accompanying drawings. 3 The single crystal X-ray diffraction test of the crystalline product of}-MOF hybrid material was carried out to analyze its precise electronic structure; and a series of characterizations were carried out on the final product, such as powder X-ray diffraction, infrared, thermogravimetric, etc., to determine that its chemical composition formula is {[Cd 12 (npd) 12 (tpt) 4 (H 2 O) 2 ](H 2 O) 10} n . With H 2 The yield is calculated based on the amount of npd used, that is, based on the npd content in the product composition. 2- The mass of the compound that should be obtained in theory is calculated by the mass of the substance, and the ratio of the actual mass of the product to the former is the yield. 2 The Chinese chemical name of NPD is 1,4-naphthalene dicarboxylic acid, and the Chinese name of the component TPT is 2,4,6-tri(4-pyridyl)-1,3,5-triazine.
[0031] 1. The present invention contains a variety of tri-nuclear clusters {Cd 3 Preparation of}-MOF hybrid materials
[0032] Example 1
[0033] Take materials according to the following specific mass or volume: H 2 npd(10.8mg,0.05mmol),tpt(15.6mg,0.05mmol),Cd(NO 3 ) 2 ·4H 2 O (30.8 mg, 0.1 mmol), CH 3 CN (9 mL), H 2 O(1mL),HNO 3 Solution (concentration 7 mol / L, 25 μL, 0.175 mmol). 2 npd:tpt:Cd(NO 3 )2 ·4H 2 O:HNO 3 The molar ratio of the substance is 1:1:2:3.5. The above materials are placed in a 25mL polytetrafluoroethylene liner, stirred for about 30 minutes, sealed in a stainless steel reactor, and the reactor is placed in an electric blast oven and heated to 120°C. After constant temperature reaction for 3 days, it is naturally cooled to room temperature to obtain a block crystal sample, which is filtered from the mother liquor, washed with distilled water, and dried naturally in the air at room temperature.
[0034] The prepared crystal samples were tested for powder diffraction using a Shimadzu XRD-6100 X-ray diffractometer (see Figure 1 , horizontal axis - angle; vertical axis - diffraction intensity), the peak of the test spectrum matches well with the peak of the crystal structure simulation spectrum (software Mercury), indicating that the structure of the obtained crystalline sample is the same as the structure obtained from the single crystal data, indicating that the sample has high phase purity.
[0035] Thermogravimetric analysis of the obtained crystalline sample showed (see Figure 2 , nitrogen atmosphere, horizontal axis - temperature; vertical axis - residue), from Figure 2 It can be seen that the crystal sample of the porous MOF hybrid material loses 3.45% of its weight before 70°C, and almost all the guest water molecules are released (theoretical calculation value 3.34%); it loses 4.11% of its weight at 280°C, and almost all the guest water molecules and coordinated water molecules are released (theoretical calculation value 4.01%). Data analysis shows that the obtained MOF hybrid material has high thermal stability. The infrared spectrum of the sample is at 3364cm -1 There is absorption near the surface, indicating that there are hydroxyl groups or molecules in the structure. After 360℃, there is obvious weight loss, which may be the collapse or decomposition of the skeleton. This shows that the porous {Cd 3}-MOF hybrid materials have good thermal stability.
[0036] Determination of single crystal structure: Select appropriate single crystals and use a SMARTAPEX II single crystal diffractometer (Mo-Ka, Graphite monochromator), X-ray diffraction data were collected at low temperature of 100(2)K and corrected by Lp factor. The crystal structure was solved by direct method, and the structure analysis and refinement were completed by SHELXTL-97 program package, and then the full matrix least squares method F was used. 2 Anisotropic refinement was performed on all non-hydrogen atoms. The hydrogen atom coordinates of the organic ligands were obtained by theoretical hydrogenation. The main crystallographic data are shown in Table 1; the coordination bond lengths are shown in Table 2.
[0037] Table 1 Main crystallographic data
[0038]
[0039] *R 1 =Σ||F o |-|F c || / Σ|F o |,wR 2 =[Σ w (F o 2 -F c 2 ) 2 / Σ w (F o 2 ) 2 ] 1 / 2
[0040] Table 2 Some coordination bond lengths
[0041]
[0042] Based on the above characterization data, the prepared {Cd 3 The general formula of the hybrid MOF material is {[Cd 12 (npd) 12 (tpt) 4 (H 2 O) 2 ](H 2 O) 10} n The structural unit chemical formula is C 216 H 144 N 24 O 60 Cd 12 , chemical formula weight is 5384.43, wherein element analysis calculated value (%): C 48.18, H 2.70, N 6.26, Cd 25.05; CHN actual measured value (%): C 48.14, H 2.67, N 6.24. Figure 3 The infrared spectrum of the new substance of the present invention (abscissa - wave number; ordinate - transmittance). FT-IR (KBr, cm -1 ): 3364(w), 3066(w), 1520(vs), 1448(m), 1350(s), 1253(m), 1052(m), 838(s), 788(s), 653(s), 580(w). Note: Elemental analysis values were obtained by Perkin-Elmer 2400 elemental analyzer; infrared spectrum was obtained by Perkin-Elmer FT-IR Spectrometer with KBr as base at 400-4000cm -1 Measured within the range.
[0043] By analyzing its single crystal X-ray diffraction data, we can obtain the precise microscopic electronic structure, i.e., the crystal structure. 3 The asymmetric unit of the crystal structure of the}-MOF hybrid material contains 12 crystallographically independent Cd 2+ ions, 12 npd 2- , 4 tpt, 2 coordinated water molecules and 10 lattice water molecules. Figure 4 As shown in a, the organic component npd 2- Four coordination modes were adopted, bridging two Cd 2+ ions or 3 Cd 2+ ions or 4 Cd 2+ Ion; Cd 2+ Among the coordination numbers of ions, Cd2, Cd3, Cd5, and Cd11 have a coordination number of 7, and the remaining Cd 2+ The coordination number of the ion is 6; the bond lengths of Cd-O and Cd-N range from Organic component npd 2- The coordination modes of tpt and tpt are shown in formulas III to VII, where M represents metal Cd 2+ Ion; Cd 2+ With carboxylate, pyridine N and water molecules, four different trinuclear clusters {Cd 3}( Figure 4 b), the coordination mode is shown in formula VIII to XI, and its composition, Cd(II) internuclear distance The parameters of the angle between the nuclei (°) are shown in Table 3.
[0044] Table 3 Tri-core cluster {Cd 3} composition, internuclear distance Angle between nuclei (°)
[0045]
[0046] like Figure 5 As shown, in {Cd 3 In the spatial structure of}-MOF hybrid materials, [Cd 3 There is a π…π interaction between the aromatic rings of the (tpt) structural unit, and the interplanar spacing Then form supramolecular chain [Cd 3 (tpt)] n ; The above three-core cluster {Cd 3} can be simplified to 7 connected nodes, organic component npd 2- and tpt components bridge the trinuclear cluster {Cd 3}, forming a composition of [Cd 12 (npd) 12 (tpt) 4 (H 2O) 2 ] of a three-dimensional metal-organic framework {Cd 3}-MOF, which can be simplified to a 3,7-connected two-node topology network. 3 In}-MOF, there are two different tunnels, A and B, with cross-sectional dimensions of and {Cd 3 The porosity of}-MOF calculated by Platon is 22.6%.
[0047] At room temperature, the {Cd 3 Fluorescence spectra of}-MOF hybrid materials ( Figure 6 , horizontal axis - wavelength; vertical axis - intensity). Spectral data analysis shows that its fluorescence emission wavelength is in a wide range of 490-800nm, with a peak wavelength at 580nm, and there are also strong shoulder peaks at 522nm and 547nm. The emitted fluorescence can be attributed to yellow-green light. The excitation wavelength is in the range of 315-500nm, and 404nm, 422nm and 467nm can all excite and produce fluorescence.
[0048] This embodiment is repeated several times, and the actual result is {Cd 3 The mass of the}-MOF hybrid material was maintained at 13.9-16.9 mg, based on H 2 The calculated yield of npd is 62.0% to 75.3%.
[0049] Example 2
[0050] Take materials according to the following specific mass or volume: H 2 npd(10.8mg,0.05mmol),tpt(15.6mg,0.05mmol),Cd(NO 3 ) 2 ·4H 2 O (30.8 mg, 0.1 mmol), CH 3 CN (1 mL), H 2 O (9 mL), HNO 3 Solution (concentration 7 mol / L, 50 μL, 0.35 mmol). 2 npd:tpt:Cd(NO 3 ) 2 ·4H 2 O:HNO 3The molar ratio of the substance is 1:1:2:7. The above materials are placed in a 25mL polytetrafluoroethylene liner, stirred for about 30 minutes, sealed in a stainless steel reactor, and the reactor is placed in an electric blast oven and heated to 100°C. After constant temperature reaction for 5 days, it is naturally cooled to room temperature. The block crystal sample is filtered from the mother liquor, washed with distilled water, and dried naturally in the air at room temperature.
[0051] The product was characterized by powder X-ray diffraction (see Figure 1 ), the data obtained are similar to those in Example 1. This indicates that the crystal structure of the sample obtained in Example 2 has not changed, and the sample has high phase purity.
[0052] This embodiment is repeated several times, and the actual result is {Cd 3 The mass of the}-MOF hybrid material was maintained at 12.1-13.5 mg, based on H 2 The calculated yield of npd is 53.9% to 60.2%.
[0053] Example 3
[0054] Take materials according to the following specific mass or volume: H 2 npd(10.8mg,0.05mmol),tpt(15.6mg,0.05mmol),Cd(NO 3 ) 2 ·4H 2 O (30.8 mg, 0.1 mmol), CH 3 CN (7 mL), H 2 O (3 mL), HNO 3 Solution (concentration 7 mol / L, 10 μL, 0.07 mmol). 2 npd:tpt:Cd(NO 3 ) 2 ·4H 2 O:HNO 3 The molar ratio of the substance is 1:1:2:1.4. The above materials are placed in a 25mL polytetrafluoroethylene liner, stirred for about 10 minutes, sealed in a stainless steel reactor, and the reactor is placed in an electric blast oven and heated to 160°C. After constant temperature reaction for 3 days, it is naturally cooled to room temperature. The block crystal sample is filtered from the mother liquor, washed with distilled water, and dried naturally in the air at room temperature.
[0055] The product was characterized by powder X-ray diffraction (see Figure 1 ), the data obtained are similar to those in Example 1. This indicates that the crystal structure of the sample obtained in Example 3 has not changed, and the sample has high phase purity.
[0056] This embodiment is repeated several times, and the actual result is {Cd 3The mass of the}-MOF hybrid material was maintained at 13.1-15.2 mg, based on H 2 The calculated yield of npd is 58.4% to 67.8%.
[0057] Second, the present invention 3 Preliminary applications of}-MOF hybrid materials
[0058] Example 4 Preparation of tunable white light HLED device
[0059] In the experiment, ordinary capped purple LED chips were used for packaging, and the chip power was about 1W. 3 The}-MOF hybrid material was ground into powder and encapsulated into an LED chip as a single-component ordered hybrid phosphor. After curing for 72 hours, a hybrid light-emitting diode HLED that can emit white light was obtained.
[0060] The luminescence spectrum of the device was tested under a steady current of 30mA (voltage 3V). Figure 7 The luminous spectrum, chromaticity coordinates and photos of the device before and after emitting light (horizontally - wavelength, vertically - intensity) of the HLED device when it is working. Data analysis shows that the correlated color temperature of the light emitted by the device when it is working is 7272K, the color rendering index CRI Ra is 65.0, and the main wavelength is 511.3nm; the photos of the device at work show that the light emitted is slightly green white light. In the CIE1931 chromaticity diagram, the spectral data corresponds to the color coordinates (0.2917, 0.3604), and the coordinates are biased towards the green light area; therefore, the actual light color is consistent with the color indicated by the coordinates. In the spectrum diagram, the emission wavelength range is 400-760nm, which basically covers the visible light band.
[0061] Experimental studies have found that by controlling the current intensity and driving the device with a current of 10 to 30 mA, the relative intensity of green light in the normalized spectrum of white light emitted by the device gradually decreases, and the correlated color temperature increases from 5536K [chromaticity coordinates (0.3318, 0.4081)] to 7272K [chromaticity coordinates (0.2917, 0.3604)]. Figure 8 As shown. From the perspective of relative intensity change, as the driving current increases, the relative intensity of green light in the 500-570nm band decreases, while the relative intensity of blue-violet light in the 400-450nm band increases, and the white light gradually becomes colder. This adjustable characteristic may be determined by the structure and performance of the light conversion layer, and this characteristic also gives the adjustable white light hybrid device a wider potential application range.
[0062] The data of the tunable white light HLED device prepared initially show that the invention uses {Cd 3The calculated value of the metal element content in the light-conversion layer made of}-MOF hybrid material is about 25%, which is much lower than the number of metal element types and total content in inorganic phosphors. Therefore, the fluorescent hybrid material of the present invention not only saves rare earth resources, but is also more environmentally friendly, and provides experimental reference data for the development of new non-rare earth single-component fluorescent materials.
[0063] Finally, it should be noted that the above embodiments are only used to illustrate the technical solution of the present invention rather than to limit it. Although the present invention has been described in detail with reference to the preferred embodiments, those skilled in the art should understand that the technical solution of the present invention can be modified or replaced by equivalents without departing from the purpose and scope of the technical solution of the present invention, which should be included in the scope of the claims of the present invention.
Claims
1. A {Cd3}-MOF hybrid material containing multiple trinuclear clusters, characterized in that: Its general chemical formula is {[Cd 12 (npd) 12 (tpt)4(H2O)2](H2O) 10 } n , belongs to the triclinic system, and its space group is Unit cell parameters In the chemical formula, the component npd 2- It is obtained by removing two protons from an organic carboxylic acid H2npd. The structure of the component H2npd is shown in Formula I; the structure of the component tpt is shown in Formula II.
2. The {Cd3}-MOF hybrid material containing multiple trinuclear clusters according to claim 1, characterized in that: The asymmetric unit of the crystal structure of the {Cd3}-MOF hybrid material contains 12 crystallographically independent Cd 2+ ions, 12 npd 2- , 4 tpt components, 2 coordinated water molecules and 10 lattice water molecules; the organic component npd 2- Four coordination modes are adopted to bridge two Cd 2+ ions or 3 Cd 2+ ions or 4 Cd 2+ Ion; Cd 2+ Among the coordination numbers of ions, Cd2, Cd3, Cd5, and Cd11 have a coordination number of 7, and the remaining Cd 2+ The coordination number of the ion is 6; the bond lengths of Cd-O and Cd-N range from Carboxylate, pyridine N and water molecules form four different trinuclear clusters {Cd3}; the organic component npd 2- The coordination modes of tpt and tpt are shown in formulas III to VII, where M represents metal Cd 2+ Ion; Cd 2+ The coordination modes are shown in formulas VIII to XI, and the numbers on the right side of the element symbols represent the atomic numbers in the asymmetric unit.
3. The {Cd3}-MOF hybrid material containing multiple trinuclear clusters according to claim 2, characterized in that: In the spatial structure of the {Cd3}-MOF hybrid material, there is a π…π interaction between the aromatic rings of the [Cd3(tpt)] structural unit, and the interplanar spacing Then form supramolecular chain [Cd3(tpt)] n The above three-core cluster {Cd3} can be simplified to 7 connected nodes, and the organic component npd 2- The tpt component bridges the trinuclear cluster {Cd3} to form a [Cd 12 (npd) 12 (tpt)4(H2O)2], a three-dimensional metal-organic framework {Cd3}-MOF, can be simplified as a 3,7-connected two-node topological network.
4. A method for preparing a {Cd3}-MOF hybrid material containing multiple trinuclear clusters as claimed in any one of claims 1 to 3, characterized in that: The {Cd3}-MOF hybrid material is prepared by a solvothermal synthesis method using H2npd, tpt, Cd(NO3)2·4H2O and HNO3 as raw materials and a mixed solution of acetonitrile and water as a solvent.
5. The method for preparing a {Cd3}-MOF hybrid material containing multiple trinuclear clusters according to claim 4, characterized in that: The preparation method specifically comprises the following steps: (1) Mixing the above raw materials and solvent to form a reaction system, and placing it in a closed container; the molar ratio of the raw materials H2npd, tpt, Cd(NO3)2·4H2O and HNO3 is 1:1:2:1.4-7.0; the volume ratio of the solvent acetonitrile and water is 1-9:1-9; (2) The reaction system is stirred at room temperature for 10 to 30 minutes, and then the reaction temperature is raised to 100 to 160° C. and reacted for 3 to 5 days, followed by natural cooling, filtration, and drying to obtain block crystals.
6. The method for preparing a {Cd3}-MOF hybrid material containing multiple trinuclear clusters according to claim 5, characterized in that: The molar ratio of H2npd, tpt, Cd(NO3)2·4H2O and HNO3 in step (1) is 1:1:2:3.
5.
7. The method for preparing a {Cd3}-MOF hybrid material containing multiple trinuclear clusters according to claim 5, characterized in that: The initial molar concentration of H2npd in the reaction system is 5 mmol / L.
8. The method for preparing a {Cd3}-MOF hybrid material containing multiple trinuclear clusters according to claim 5, characterized in that: The reaction temperature in step (2) is 120° C., and the drying refers to washing the crystals with distilled water and then drying them naturally in the air at room temperature.
9. Application of a {Cd3}-MOF hybrid material containing multiple trinuclear clusters, characterized in that: The use of the {Cd3}-MOF hybrid material prepared by any method described in claims 4 to 8 in the preparation of HLED, the prepared hybrid light-emitting diode HLED can emit adjustable white light that changes with the current intensity when working, and the wavelength of the white light covers the visible light band of 400-760nm.
10. An application of a {Cd3}-MOF hybrid material containing multiple trinuclear clusters, characterized in that: Use of the {Cd3}-MOF hybrid material prepared by the method described in any one of claims 4 to 8 in the preparation of composite fluorescent materials.
Citation Information
Patent Citations
Double-metal porous complex and preparation method thereof
CN106832316A
Dual-core-based three-node MOF material and preparation method thereof, and application of dual-core-based three-node MOF material in preparation of warm white light LED
CN116948196A
Three-dimensional coordination polymerization {Cdn}-MOF fluorescent material, preparation method thereof and application of fluorescent material in preparation of green light LED
CN118027433A
